Addressing consequences of school closure on oral health care of children during COVID-19 - Chhibber, Radhika; Shrivastava, Richa; Tandale, Madhura (Frontiers in Pediatrics, 2022)
School closures are known to result in impacts to nutrition and oral health in children1. Initial studies have found negative influences of school closures on dental care in children, particularly among the most vulnerable2. In the US, children in 2020 were 75% more likely to have poor oral health than in 20193, highlighting a cause for concern. In India, the closure of schools has resulted in food insecurity, as many have faced difficulties without access to school-based nutrition programs4. Recommendations are made to draw attention to the oral health and nutrition of school children. Teachers, researchers, dental professionals and the government all have a role to play in the recovery of oral hygiene and nutrition amongst school children, from providing support, information, understanding effects and offering funding for further research.